Perancangan Rem Cakram Roda Depan Pada Motor Yamaha Vega RR 2014 - Hazzel Giervin Putra Hengky; Viktor Naubnome (Jurnal Ilmiah Wahana Pendidikan, 2022)
Intense competition in the industry, especially in the automotive world, is bound to make vehicles better and easier for vehicle users. This includes using the brakes on two-wheeled vehicles. From the calculation results of the front disc brake of the motorcycle Yamaha Vega RR 2014, it can be concluded that several large forces are transmitted for each braking operation, namely from the piston force (Fpiston) = 31.81 Kgf, the force on the piston pressure canvas (F) = 203.66 Kgf (2 canvases) and Braking Force (????????) = 69.71 Kgf. Therefore, the final result of the life calculation for the Yamaha Vega RR 2014 disc brake pads is 800 hours. Assuming that the vehicle is used for an average of 3 hours a day, the service life of disc brake pads can reach 8.8 months.